Sustainable Tourism As A Catalyst For Achieving Sdgs In Indonesia - Dicky Satria Ramadhan; Tri Wahyu Yuliani; Asyifa Nur Laely Munawaroh (International Journal of Science and Environment (IJSE), 2025)
Sustainable tourism plays a strategic role as a catalyst for achieving the Sustainable Development Goals (SDGs) in Indonesia, particularly in promoting economic growth and decent work. This study analyzes the impact of several factors namely, the number of tourists, tourism investment, tourism foreign exchange, and the average length of tourist stays on the achievement of the SDGs in Indonesia. It utilizes secondary data from the Central Bureau of Statistics and the Ministry of Tourism and Creative Economy, covering the period from 2000 to 2023. The data analysis employs multiple linear regression, along with classical assumption testing and statistical hypothesis testing. The results indicate that both the number of tourists and domestic tourism investment positively influence the achievement of the SDGs in Indonesia. This suggests that sustainable tourism development can create decent jobs and enhance the income of local communities. Moreover, tourism has the potential to drive regional economic growth, which can subsequently contribute to national economic growth